2019
DOI: 10.1155/2019/9639016
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Titanate from Food Waste: Combustion Synthesis, Sintering, Characterization, and Properties

Abstract: Calcium titanate (CaTiO 3 ) was combustion synthesized from a calcium source of waste duck eggshell, anatase titanium dioxide (A-TiO 2 ), and magnesium (Mg). e eggshell and A-TiO 2 were milled for 30 min in either a high-energy planetary mill or a conventional ball mill. ese powders were then separately mixed with Mg in a ball mill. After synthesis, the combustion products were leached and then sintered to produce CaTiO 3 ceramic. Analytical characterization of the as-leached combustion products revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
3
15
0
1
Order By: Relevance
“…Subsequently, as-prepared calcium titanate powder was processed by single-and two-step sintering to produce dense calcium titanate ceramics.The microstructures, densities and dielectric properties of the calcium titanate ceramics were compared and analyzed as-sintered. XRD analysis in our previous study [23] confirmed that the as-received duck eggshell was composed entirely of calcium carbonate. XRF data of the duck eggshell after heating (Table I) showed a major compound of calcium oxide (CaO) from the decomposition of CaCO 3 to form CaO and CO 2 gas.…”
Section: Introductionsupporting
confidence: 64%
See 4 more Smart Citations
“…Subsequently, as-prepared calcium titanate powder was processed by single-and two-step sintering to produce dense calcium titanate ceramics.The microstructures, densities and dielectric properties of the calcium titanate ceramics were compared and analyzed as-sintered. XRD analysis in our previous study [23] confirmed that the as-received duck eggshell was composed entirely of calcium carbonate. XRF data of the duck eggshell after heating (Table I) showed a major compound of calcium oxide (CaO) from the decomposition of CaCO 3 to form CaO and CO 2 gas.…”
Section: Introductionsupporting
confidence: 64%
“…Powdered duck eggshell and A-TiO 2 were high-energy milled with Si 3 N 4 balls in a jar (Fritsch GMBH, Pulverisette 6, Germany) for 30 min at 400 rpm. This procedure was adapted from reference works [23,24]. The high-energy milled powder mixtures were then mixed with magnesium powder by ball milling for 120 min using zirconia (ZrO 2 ) balls and a nylon vial.…”
Section: Preparation Of Calcium Titanate Powders By Combustion Synthesismentioning
confidence: 99%
See 3 more Smart Citations